Pupillary response to real, illusory, and implied motion. - Serena Castellotti (Public Library of Science (PLoS), 2021)
The perception of moving objects (real motion) is a critical function for interacting with a dynamic environment. Motion perception can be also induced by particular structural features of static images (illusory motion) or by photographic images of subjects in motion (implied motion, IM). Many cortical areas are involved in motion processing, particularly the medial temporal cortical area (MT), dedicated to the processing of real, illusory, and implied motion. Recently, there has been a growing interest in the influence of high-level visual processes on pupillary responses. However, just a few studies have measured the effect of motion processing on the pupil, and not always with consistent results. Here we systematically investigate the effects of real, illusory, and implied motion on the pupil diameter for the first time, by showing different types of stimuli (movies, illusions, and photos) with the same average luminance to the same observers. We find different pupillary responses depending on the nature of motion. Real motion elicits a larger pupillary dilation than IM, which in turn induces more dilation than control photos representing static subjects (No-IM). The pupil response is sensitive even to the strength of IM, as photos with enhanced IM (blur, motion streaks, speed lines) induce larger dilation than simple freezed IM (subjects captured in the instant they are moving). Also, the subject represented in the stimulus matters: human figures are interpreted as more dynamic and induce larger dilation than objects/animals. Interestingly, illusory motion induces much less dilation than all the other motion categories, despite being seen as moving. Overall, pupil responses depend on the individual perception of dynamicity, confirming that the pupil is modulated by the subjective interpretation of complex stimuli. We argue that the different pupillary responses to real, illusory, and implied motion reflect the top-down modulations of different cortical areas involved in their processing.